PENINGKATAN HASIL BELAJAR TEMATIK SUBTEMA KERAJAAN ISLAM DI INDONESIA DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) DI MI MA’ARIF NU MIRU LAMONGAN - Hasanah, Wulan Agustina (Journal Of Islamic Elementary School (JIES), 2018)
In the current school learning system, thematic learning still tends to be teacher-centered so that the classroom atmosphere is still rigid, and on average students are still passive in accepting learning so students cannot understand the material to the fullest. This study aims to test the application of STAD type cooperative learning in improving learning outcomes in thematic subjects. The research model used the Class Action Research (CAR) model which was adapted from Kurt Lewin which consisted of 2 cycles. The results of the study: (1) The application of the Student Teams Achievement Divisions (STAD) cooperative learning model on learning 6 Islamic Kingdom sub-themes in Indonesia can be categorized as well as evidenced by the results of teacher activity observations of 63 in the first cycle and increased to 89 in the second cycle. Likewise, the results of the observation activities of students from 67.10 in the first cycle increased to 88.15 in the second cycle. In this learning process, teachers and students are able to apply the STAD learning model well; (2) There is an increase in learning outcomes in the sub-theme of Islamic Kingdom in Indonesia learning 6 in class V of MI Ma'arif NU Miru Sekaran Lamongan after applying the STAD cooperative learning model. This is evident from the average value of social studies subject students in the Islamic Kingdom in Indonesia with 6 pre-cycle learning at 65.8 with a percentage of 40%, in the first cycle to 75.6 with a percentage of 60%, and increased to 85.2 with a percentage of 92% in cycle II. It is evident from the average value of students of Indonesian Language Subjects in Islamic Kingdom in Indonesia learning 6 in the pre cycle of 66 with a percentage of 36%, in the first cycle being 73 with a percentage of 52%, and increasing to 82.2 with a percentage of 88% in cycle II.